2021
DOI: 10.1186/s12889-021-11189-7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary, physical exercises and mental stress in a Chinese population: a cross-sectional study

Abstract: Background Mental health is affected by both genetic and environmental factors. However, previous studies have showed conflict findings about the role of lifestyle and little is known about the situation of the Chinese population. The purpose of this study was to explore the relationship between the frequency of food consumption, physical exercise condition and mental health, as well as factors related to mental stress in Chinese. Methods We recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…In addition, mounting evidence has demonstrated that fish intake may reduce the risk of cognitive function. A Chinese study presented that fish or aquatic products may reduce mental stress by improving psychological health via antioxidant action and inflammatory responses; this protective effect is more pronounced in men [55], consistent with our findings indicating that proper intake of fish was beneficial to mental health in men.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, mounting evidence has demonstrated that fish intake may reduce the risk of cognitive function. A Chinese study presented that fish or aquatic products may reduce mental stress by improving psychological health via antioxidant action and inflammatory responses; this protective effect is more pronounced in men [55], consistent with our findings indicating that proper intake of fish was beneficial to mental health in men.…”
Section: Discussionsupporting
confidence: 91%
“…In Chinese populations, the higher frequency of pickled foods intake increased the risks of mental stress. [ 78 ] More clinical attention is needed to explore the positive psychology of this population from multiple perspectives. With the social system support, the benefit finding can be improved by guiding patients to focus on the positive aspects of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…As health- socioeconomic- and cultural-related impacts of the pandemic were vastly different in Australia and the United States [ 68 ], differential effects are likely to have impacted the factors we studied across these groups, including lifestyle. While previous research has indicated a relationship between psychological distress and lifestyle factors [ 69 , 70 ], we cannot necessarily generalise these results outside of Australia and the USA. Finally, we used different tools across studies to measure psychological distress and impulsivity.…”
Section: Discussionmentioning
confidence: 82%